Canaloplasty in Open-Angle Glaucoma Surgery: A Four-Year Follow-Up - Paolo Brusini (The Scientific World Journal)
Canaloplasty is a new nonperforating surgical technique for open-angle glaucoma, in which a microcatheter is inserted within Schlemm’s canal for the entire 360 degrees. A 10-0 prolene suture, which is tied to the distal tip of the microcatheter, is then positioned and left tensioned in Schlemm’s canal, thus facilitating aqueous outflow through natural pathways. A small amount of viscoelastic agent is delivered in Schlemm’s canal while the catheter is withdrawn. The mid-term results are very promising. Based on our cohort of 214 patients, the percentages of eyes that obtained postoperative IOP ≤ 21 mmHg, ≤18 mmHg, and ≤16 mmHg with or without medical therapy after 2 and 3 years were 88.7%, 73.7%, and 46.2% (2 years); 86.2%, 58.6%, and 37.9% (3 years), respectively. The most frequent complications observed included hyphema; descemet membrane detachment; IOP spikes; and hypotony. The advantages of canaloplasty over trabeculectomy include (1) no subconjunctival bleb; (2) no need for antimetabolites; (3) fewer postoperative complications; and (4) a simplified follow-up. The disadvantages include the following: (1) a long and rather steep surgical learning curve; (2) the need of specific instruments; (3) average postoperative IOP levels tend not to be very low; and (4) impossibility to perform the entire procedure in some cases.